Chassis Influence on the Exposure Assessment of a Compact EV during WPT Recharging Operations - Valerio De Santis; Luca Giaccone; Fabio Freschi (Magnetochemistry, 2021)
In this study, the external magnetic field emitted by a wireless power transfer (WPT) system and the internal electric field induced in human body models during recharging operations of a compact electric vehicle (EV) are evaluated. The magneticfield is calculated with a hybrid scheme coupling the boundary element method with the surface impedance boundary conditions in order to fit the multiscale open-boundary characteristics of the problem. A commercial software is then used to perform numerical dosimetry. Specifically, two realistic anatomical models, both in a driving position and in a standing posture, are considered, and the chassis of the EV is modeled either as a currently employed aluminum alloy and as a futuristic carbon fiber composite panel. Aligned and misaligned coil configurations of the WPT system are considered as well. The analysis of the obtained results shows that the International Commission on Non-Ionizing Radiation Protection (ICNIRP) reference levels are exceeded in the driving position, especially for the carbon fiber chassis, whereas the system is compliant with the basic restrictions, at least for the considered scenarios.